Effectiveness of Superficial Radial Nerve Block on Pain, Function and Quality of Life in Patients With Hand Osteoarthritis: A Prospective, Randomized and Controlled Single-Blind Study - Burcu METİN ÖKMEN,; Korgün ÖKMEN,; Lale ALTAN, (Archives of Rheumatology, 2018)
Objectives: This study aims to investigate the effects of ultrasound-guided superficial branch of the radial nerve block on pain, function and quality of life in patients with hand osteoarthritis. Patients and methods: In this prospective, randomized and controlled single-blind study, 50 female patients (mean age 59.0±5.1 years; range, 46 to 64 years) diagnosed with hand osteoarthritis were randomized into two groups. Group 1 (n=25) was administered an ultrasound-guided superficial branch of the radial nerve injection (with a combination of 2 mL 0.25% bupivacaine and 1 mL methylprednisolone acetate) + exercise, while group 2 (n=25) only exercised. Patients were assessed with a visual analog scale for pain, hand grip strength, finger grip strength, Quick Disability of the Arm, Shoulder and Hand questionnaire, Duruöz Hand Index and Short-form 12. Data were obtained before treatment (W0), in the second week after treatment (W2) and in the fourth week after treatment (W4). Results: In group 1, a statistically significant improvement was obtained in all parameters at both W2 and W4 compared to the values recorded at W0 (p<0.05). In group 2, a statistically significant improvement was observed only in the parameters of hand grip strength and finger grip strength at W2 and W4 (p<0.05). A comparison of the scores of the two groups showed statistically significant superior improvement in group 1 in all parameters at both W2 and W4 (p<0.05). Conclusion: The findings of our study showed that an ultrasound-guided superficial branch of the radial nerve block combined with exercise is a significantly superior treatment to exercise-only regarding the improvements in the parameters of pain, function and quality of life in hand osteoarthritis patients.